Diorama Media Fiction Stories in Indonesian Language Subjects For Increase Skills Write Student - Nyoman Ayu Candra Purnama Dewi; Maria Goreti Rini Kristiantari; Dewi Anzelina (Universitas Pendidikan Ganesha, 2025)
Elementary school students' writing skills still need significant strengthening, considering that many of them have difficulty in developing ideas and expressing them coherently in written form. The lack of ability to explore creativity in writing indicates the need for more innovative learning strategies and facilitate comprehensive exploration of ideas. This study aims to determine the effectiveness of the Fiction Story Diorama learning media in Indonesian Language Subjects to Improve Writing Skills of Grade IV Elementary School Students. The development model used is the ADDIE model. The subjects of this study were 18 grade IV students. Data collection methods and instruments used interviews, questionnaires and tests. The data analysis techniques used in this study were quantitative, qualitative and inferential descriptions. The results of the effectiveness test of this media were tested through a post-test, which showed that the concrete media